2022
DOI: 10.3390/cancers14112596
|View full text |Cite
|
Sign up to set email alerts
|

BERENICE Final Analysis: Cardiac Safety Study of Neoadjuvant Pertuzumab, Trastuzumab, and Chemotherapy Followed by Adjuvant Pertuzumab and Trastuzumab in HER2-Positive Early Breast Cancer

Abstract: BERENICE (NCT02132949) assessed the cardiac safety of the neoadjuvant–adjuvant pertuzumab–trastuzumab-based therapy for high-risk, HER2-positive early breast cancer (EBC). We describe key secondary objectives at final analysis. Eligible patients received dose-dense doxorubicin and cyclophosphamide q2w × 4 ➝ paclitaxel qw × 12 (Cohort A) or 5-fluorouracil, epirubicin, cyclophosphamide q3w × 4 ➝ docetaxel q3w × 4 (B) as per physician’s choice. Pertuzumab–trastuzumab (q3w) was initiated from the taxane start and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…A comprehensive pooled safety analysis is challenging because safety data were not collected and reported in the same way in all studies. Safety data from the individual studies has been extensively reported, and suggest that toxicity is not markedly increased with the addition of pertuzumab except for diarrhea which is higher particularly in the neoadjuvant setting where it is given concurrently with chemotherapy ( Table S3 ; [ 5 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 ]). Docetaxel plus pertuzumab and trastuzumab was compared with docetaxel plus trastuzumab for treatment of HER2-positive EBC in the NEOSPHERE trial [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A comprehensive pooled safety analysis is challenging because safety data were not collected and reported in the same way in all studies. Safety data from the individual studies has been extensively reported, and suggest that toxicity is not markedly increased with the addition of pertuzumab except for diarrhea which is higher particularly in the neoadjuvant setting where it is given concurrently with chemotherapy ( Table S3 ; [ 5 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 ]). Docetaxel plus pertuzumab and trastuzumab was compared with docetaxel plus trastuzumab for treatment of HER2-positive EBC in the NEOSPHERE trial [ 14 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of the 199 patients (6.5%) in Cohort A and four of the 198 (2.0%) patients in Cohort B had symptomatic and asymptomatic LVEF declines to <50% and by ≥10 percentage points from baseline. The 5-year follow-up data showed a similarly low incidence of cardiac toxicity [ 24 ]. These data suggest an acceptable cardiac toxicity profile with the addition of pertuzumab to trastuzumab and these chemotherapy regimens, and thus support the safety of continuation of pertuzumab plus trastuzumab from the neoadjuvant to adjuvant setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is approved by FDA for use in association with trastuzumab and docetaxel in MBC, and in combination with trastuzumab and chemotherapy as neoadjuvant or adjuvant therapy in non-metastatic disease. The combination of pertuzumab and trastuzumab has shown low cardiac toxicity and favorable efficacy outcomes as demonstrated by the BERENICE study [ 224 ].…”
Section: Breast Cancer Therapiesmentioning
confidence: 99%
“…Cardiac safety was the primary endpoint: left ventricular systolic dysfunction (LVSD) incidence was low (5.6%) in the neoadjuvant setting in the anthracycline-containing arm ( 29 ). Furthermore, the BERENICE trial demonstrated cardiac safety in both dose-dense and standard anthracycline-containing regimens in combination with trastuzumab and pertuzumab ( 30 , 31 ).…”
Section: Review Of Neoadjuvant Trialsmentioning
confidence: 99%